Reframing Gender and Sacred Balance: Konstruksi Makna Simbolik Tari Baris Kekupu Banjar Lebah dalam Film Dokumenter - I Wayan Eka Saputra; Freddy Hendrawan; Ni Made Emmi Nutrisia Dewi; Ramanda Dimas Surya Dinata (Besaung : Jurnal Seni Desain dan Budaya, 2026)
This study examines the construction of symbolic meaning in gender transformation within the Baris Kekupu dance of Banjar Lebah through the medium of documentary film. Previous studies tend to frame gender transformation merely as a shift in performer roles; however, this research positions it as a process of reinterpreting meaning in relation to sacred values in Balinese culture. Drawing upon the concept of Rwa Bhineda - a principle of balance between two opposing yet complementary forces - this study argues that the presence of female dancers in Baris Kekupu does not diminish its sacredness but instead represents a symbolic balance between masculinity and femininity. This research employs a qualitative approach with semiotic analysis based on Ferdinand de Saussure, focusing on the relationship between signifier and signified within the visual and narrative elements of the documentary film. Data were collected through observation, interviews, questionnaires, and literature review, and were integrated into the production of an expository documentary film structured using a three-act narrative framework. The findings reveal that the meaning of gender transformation is constructed through aesthetic elements such as movement, costume, and butterfly symbolism, and further reinforced through cinematographic techniques that shape visual narratives. This study demonstrates that documentary film functions not only as a medium of documentation but also as a cultural design practice that actively reframes public perception of gender and sacredness. Thus, the concept of Reframing Gender and Sacred Balance provides a critical framework for understanding gender transformation as an integral part of cultural equilibrium in Balinese tradition